L'arithmetique de l'emigration selon Milan Kundera - Coutinho, Ana Paula (2007)
Milan Kundera, a Czech emigrant, naturalized French in 1981, who has beenwriting in French since 1995, is one of the most famous examples of the migrant voice's incorporation in current French literature. Taking his novel L'ignorance, published in 2003, as a starting point, we try to articulate the traces of the " arithmétique de l'émigration" (emigration's arithmetic) that the author developed in Les Testaments Trahis as a kind of exercise ofapplication the results of which also represent an essay of auto-reference deferred.